Non-Pathogenic Mopeia Virus Induces More Robust Activation of Plasmacytoid Dendritic Cells than Lassa Virus - Schaeffer, Justine (Viruses, 2019)
Lassa virus (LASV) causes a viral haemorrhagic fever in humans and is a major public health concern in West Africa. An efficient immune response to LASV appears to rely on type I interferon (IFN-I) production and T-cell activation. We evaluated the response of plasmacytoid dendritic cells (pDC) to LASV, as they are an important and early source of IFN-I. We compared the response of primary human pDCs to LASV and Mopeia virus (MOPV), which is very closely related to LASV, but non-pathogenic. We showed that pDCs are not productively infected by either MOPV or LASV, but produce IFN-I. However, the activation of pDCs was more robust in response to MOPV than LASV. In vivo, pDC activation may support the control of viral replication through IFN-I production, but also improve the induction of a global immune response. Therefore, pDC activation could play a role in the control of LASV infection.